2016
DOI: 10.1071/cp15233
|View full text |Cite
|
Sign up to set email alerts
|

Resource-use maximisation through legume intercropping with maize in the eastern Himalayan region of India

Abstract: Intercropping provides opportunity to harness available resources. Thus, maize intercropped with soybean or peanut (groundnut) was tested with 1 : 1, 1 : 2, and 1 : 5 row proportions along with sole plantings of each crop to measure resource capture and resource-use efficiency. Results revealed that sole peanut had 60% higher maize-equivalent yield and 55% better production efficiency, followed by the 1 : 5 row proportion of maize–peanut, over sole maize. Intercropping increased land-use efficiency by 17–53% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The K acquisition of three intercropping systems was enhanced by 22.5% comparable with the values expected based on the higher biomass production compared to sole crops (Wang et al, 2015b). This greater K acquisition in line with biomass overyielding has been observed more often (Choudhary et al, 2016;Singh and Ahlawat, 2012). Analyzing dynamics over the season Zhang et al (2017) observe that cumulative K acquisition (per unit area basis) of intercropped crops was significantly lower than that of sole crops during early growth stages, and gradually showed higher K acquisition toward harvest.…”
Section: Potassiumsupporting
confidence: 71%
“…The K acquisition of three intercropping systems was enhanced by 22.5% comparable with the values expected based on the higher biomass production compared to sole crops (Wang et al, 2015b). This greater K acquisition in line with biomass overyielding has been observed more often (Choudhary et al, 2016;Singh and Ahlawat, 2012). Analyzing dynamics over the season Zhang et al (2017) observe that cumulative K acquisition (per unit area basis) of intercropped crops was significantly lower than that of sole crops during early growth stages, and gradually showed higher K acquisition toward harvest.…”
Section: Potassiumsupporting
confidence: 71%
“…Under mixed cropping conditions, plants experience stress in the form of abiotic stresses such as light, nutrients, water, light and temperature, and biotic stress due to the presence of other plants and pests, or even a high concentration of heavy metals (Choudhary et al 2016;Dhar et al 2013;Taberima et al 2020;Wang et al 2017). In this study, all plants were under stress due to the marginal conditions of the growing media (without additional fertilization) and the limited supply of water.…”
Section: Selection Of Adaptive Varieties In T'sen Cropping Patternsmentioning
confidence: 76%
“…Intercropping was found to be more beneficial (indicated by LER greater than a unit) in less fertile fields and more marginal environments compared to fertile fields (Kermah et al (2017). Choudhary et al (2016) observed that intercropping increased land-use efficiency by 17-53 % and produced a LER of 1.21-1.56.…”
Section: Effect Of Cowpea Population Density and Row Orientation On S...mentioning
confidence: 94%